READING NARRATIVE BY SEMANTIC MAPPING: A STRATEGY TO ENHANCE STUDENTS’ COMPREHENSION - Durratul Hikmah; Mohammad Sofyan Adi Pranata (UIN Raden Mas Said Surakarta, 2019)
This study attempted to investigate the effectiveness of using semantic mapping strategy for improving students’ reading comprehension skill on narrative text. This study employed a quasi-experimental design by dividing the research group into control and experimental group. In this study, a pre-test and post-test experimental design with control group was used. The instruments used to collect the data were reading comprehension tests before and after the treatment. The study was conducted at grade VIII of SMP Nurul Jadid Probolinggo at which the students were identified as having problem in comprehending English narrative text. The finding showed that semantic mapping strategy can improve students’ comprehension on reading narrative text.